The Diversity of Butterfly (Lepidoptera: Rhopalocera) in Triagle of Lakes Lumajang, East Java - Afandi, Afandi; Purwatiningsih, Purwatiningsih; Prihatin, Jekti (Jurnal ILMU DASAR, 2023)
The triangle of lakes which are Bedali Lake, Klakah Lake and Pakis Lake area serves as a sanctuary for many wildlife including butterflies. Butterfly spesies at Ranu Bedali has ecological functions as herbivors, pollination, detrivor, as well as bioindicator of ecosystem changes. The objective of this study was to identify the diversity of butterflies in triangle of lakes Lumajang Regency. The sampling technique used was Abundance Point Index Method. All spesies captured were identified and analyzed. The results showed that the composition of butterflies have been obtained consisted of 4 families and 37 species. The most abundant family with a huge of species is Nymphalidae while the least family is Lycaenidea. The diversity index (H’) for the butterflies in Pakis Lake, Klakah Lake and Bedali Lake were 2.56; 2.73 and 2.76 respectively. The evenness index (E) for the butterflies in Pakis Lake, Klakah Lake and Bedali Lake were 0.43; 0.47 and 0.48 respectively. Among the butterlies, it found Troides helena was classified at the list of Appendix I and Appendix II CITES (Convention on International Trade in Endangered).